Inflammatory stress potentiates emodin-induced liver injury in rats - Tu, Can; Gao, Dan; Li, Xiao-Fei; Li, Chun-Yu; Li, Rui-Sheng; Zhao, Yan-Ling; Li, Na; Jia, Ge-Liu-Chang; Pang, Jing-Yao; Cui, He-Rong; Ma, Zhi-Jie; Xiao, Xiao-He; et al. (Frontiers in Pharmacology, 2015)
Herbal medicines containing emodin, widely used for the treatment of hepatitis in clinic, have been reported with hepatotoxicity in individuals. A modest inflammatory stress potentiating liver injury has been linked to the idiosyncratic drug-induced liver injury (IDILI). In this study, we investigated the hypothesis that lipopolysaccharide (LPS) interacts with emodin could synergize to cause liver injury in rats. Emodin (ranging from 20, 40 to 80 mg/kg), which is in the range of liver protection, was administered to rats, before LPS (2.8 mg/kg) or saline vehicle treatment. The biochemical tests showed that non-toxic dosage of LPS coupled with emodin caused significant increases of plasma ALT and AST activities as compared to emodin alone treated groups (P<0.05). In addition, with LPS or emodin alone could not induce any changes in ALT and AST activity, as compared with the control group (0.5% CMC-Na treatment). Meanwhile, the plasma proinflammatory cytokines, TNF-α, IL-1β, and IL-6 increased significantly in the emodin/LPS groups compared to either emodin groups or the LPS (P<0.05). Histological analysis showed that liver damage was only found in emodin/LPS cotreatmented rat livers samples. These results indicate that non-toxic dosage of LPS potentiates the hepatotoxicity of emodin. This discovery raises the possibility that emodin and herbal medicines containing it may induce liver injury in the inflammatory stress even in their therapeutic dosages.